2019
DOI: 10.3390/ijerph16050844
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Embryo Development and Behavioral Response of Medaka Fish under Static Magnetic Field Exposures

Abstract: The static magnetic field (SMF) in human exposure has become a health risk concern, especially with respect to prolonged exposure. The International Commission on Non-Ionizing Radiation Protection (ICNIRP) has been considering cell or animal models to be adopted to estimate the possible human health impacts after such exposure. The medaka fish is a good animal model for human-related health assessment studies; this paper examines both the embryo development and behavioral responses in medaka fish in vivo to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…The magnetic flux density within the embryo exposure region was between 80-100 mT measured by a GM05 Gaussmeter. Details of the experimental set up is according to the pilot study as previously reported [12]. The setup is illustrated in (Figures 1-3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic flux density within the embryo exposure region was between 80-100 mT measured by a GM05 Gaussmeter. Details of the experimental set up is according to the pilot study as previously reported [12]. The setup is illustrated in (Figures 1-3).…”
Section: Methodsmentioning
confidence: 99%
“…Amara [11] investigated the effects of SMF to 128 mT with 1 hour per day for a consecutive 30 days exposure together with anti-oxidative enzymes activity in a male rat brain; the study indicated that the exposure to SMF will induce oxidative stress in the rat's hippocampus and frontal cortex. Sun [12] has adopted medaka fish to investigate the embryo development as a pilot in-vivo study with no observable impact on the embryo development rate under prolonged SMF exposure. However, unusual abnormal growth was observed in some embryo samples of the treated groups.…”
Section: Introductionmentioning
confidence: 99%
“…The Medaka fish was chosen in the paper by Sun et al [8] to address the effect of long term (entire development period) static magnetic field exposure at the mT level on embryo development and behavioral response. Development was not affected whereas swimming velocity was reduced in the exposed group.…”
Section: About the Papers Of This Special Issuementioning
confidence: 99%
“…Therefore, the behavior of zebrafish, such as approach-avoidance, cognitive, schooling behavior, social paradigms, and locomotion, offers a possible model to evaluate any neuron-stimulated impact [16][17][18][19][20]. Among many behaviors, zebrafish locomotion is usually selected [15,20,23,24], and it has been solved as time-series [20] similarly to other animal model studies, e.g., the flying track of the Drosophila melanogaster [25].…”
Section: Introductionmentioning
confidence: 99%
“…The empirical method used to solve this problem in other studies is to place the fish in the experimental environment long enough, e.g., 24 h before the experiment. The results of other studies have supported that this method could effectively reduce the stimulation of zebrafish by surrounding environmental factors, but this still needs the verification support of quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%